Kearifan Lokal dan Mediasi Digital: Analisis Ekologis Pengasuhan Digital Orang Tua Anak Usia Dini - Muslihatun Maulidian; Aulia Dwi Amalina; Ratin Wahyu Juni Atma (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2026)
Parental caregiving in the use and management of digital media (digital parenting) has become an important issue in early childhood education, particularly in semi-peripheral areas characterized by strong collective family traditions and relatively low digital literacy. This study aims to explore digital parenting practices among parents of early childhood children in East Lombok by integrating Bronfenbrenner’s ecological systems theory and Livingstone’s parental mediation framework. This study used a descriptive-exploratory approach by distributing questionnaires to 105 parents in four subdistricts in East Lombok. The results show three dominant parenting patterns in the use of digital technology, namely restrictive at 38.1%, permissive at 29.5%, and authoritative at 32.4%, each of which was influenced by the intersection of microsystem, mesosystem, and exosystem factors. An important finding of this study indicates that intergenerational value conflict within the Sasak extended family structure acts as a mediating factor that disrupts parental consistency in mediating children’s use of digital media. In addition, parents’ digital literacy, rather than educational level alone, is the main determinant distinguishing adaptive and maladaptive digital parenting strategies. The conclusion of the study affirms that digital parenting practices in rural-collective communities require an approach that is contextual, family-based, and responsive to local cultural values. The implications of this study provide theoretical contributions to the development of parental mediation studies in the Global South context, as well as practical implications for families, educators, and communities in developing a community-based digital parenting model that integrates Sasak local wisdom, particularly the concept of adat as a mechanism of social control.